Design a low cost and simple microwave vector reflctometer [electronic resource] - Nur Syuhana Khalid, 1989- , author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2013